A Next Generation Formulation of Curcumin Ameliorates Experimentally Induced Osteoarthritis in Rats via Regulation of Inflammatory Mediators - Yabas, Mehmet; Orhan, Cemal; Er, Besir; Tuzcu, Mehmet; Durmus, Ali Said; Ozercan, Ibrahim Hanifi; Sahin, Nurhan; Bhanuse, Prakash; Morde, Abhijeet Ashok; Padigaru, Muralidhara; Sahin, Kazim (Frontiers in Immunology, 2021)
Osteoarthritis (OA) is a chronic and debilitating disease of the knee joint. OA of the knee is initiated by physical damage and accumulated oxidative stress, followed by an exaggerated inflammation leading to cartilage damage. Currently, no effective and safe therapeutic option capable of restoring articular cartilage tissue and joint architecture is available. We here report a novel and highly bioavailable formulation of curcumin, labeled as Next Generation Ultrasol Curcumin (NGUC), which was 64.7 times more bioavailable than natural 95% curcumin extract as demonstrated in rat bioavailability studies. We further investigated the protective effect of NGUC against monosodium iodoacetate (MIA)‐induced knee OA in rats. Analysis of X-ray and histopathological images revealed that NGUC supplementation restored joint architecture and reduced swelling of joints induced by MIA. NGUC treatment caused a significant reduction in the levels of inflammatory mediators such as TNF-, IL-1, IL-6, COMP, and CRP, and expressions of MMP-3, 5-LOX, COX-2, and NFB in synovial tissue of rats with MIA-induced OA. NGUC also decreased serum MDA level and increased the levels of antioxidant enzymes SOD, CAT, and GPX. Thus, our results indicate that a novel formulation of curcumin with enhanced bioavailability effectively ameliorates the pathophysiology of OA.